Artificial Intelligence Adoption and Marketing Performance among SMEs: Examining Technological, Organizational, and Environmental Barriers through the TOE Framework - Sarah Dien Hawa; Sudarto Sudarto; Najmudin Najmudin; Weni Novandari (ICON Publisher, 2026)
Artificial Intelligence (AI) has emerged as a strategic technology capable of enhancing organizational competitiveness and marketing effectiveness. However, many Small and Medium Enterprises (SMEs), particularly in emerging economies, continue to face significant challenges in adopting AI technologies. This study aims to examine the influence of technological barriers, organizational barriers, and environmental barriers on AI adoption and their implications for marketing performance among SMEs in Banyumas Regency, Indonesia. The study adopts the Technology–Organization–Environment (TOE) framework as the theoretical foundation for explaining AI adoption behavior within SMEs. A quantitative research approach was employed using survey data collected from 100 SMEs in Banyumas. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that technological barriers and environmental barriers significantly influence AI adoption, whereas organizational barriers do not significantly affect AI adoption. Furthermore, AI adoption significantly influences marketing performance. The results indicate that SMEs adopting AI technologies experience improvements in sales growth, customer satisfaction, customer loyalty, digital campaign effectiveness, market responsiveness, and competitive advantage. The study contributes theoretically by extending the TOE framework through the integration of multidimensional barriers and AI-driven marketing performance. Practically, the findings provide important implications for SME owners, policymakers, and technology providers in designing strategies to accelerate AI adoption and strengthen SME competitiveness in the digital economy. The study also highlights the importance of technological readiness and supportive digital ecosystems in facilitating successful AI implementation among SMEs.